Brassica oleracea var. botrytis (cauliflower) as a replacement for a white rice diet - Mahajidin, Nurul Hanis; Mohd Shukry, Fatin Nuraishah; Yaafar, Mohd Rabani; Zulkipli, Husna; Che Mat, Ahmad Nazeer (2024)
This study aims to determine the calorie content and additional nutrional benefits of cauliflower compared to white rice as well as their antibacterial properties. Brassica oleracea var. botrytis also known as cauliflower, is a commonly consumed vegetable of the Brassicaceae family that is rich in dietary fibre, vitamins, minerals, and bioactive compounds. Unlike white rice, which is high in carbohydrates and contains minimal nutritional value, cauliflower is low in calories and also offers essential nutrients for a healthy diet. The calorie contents of cauliflower and white rice was determined by food calorimetry. In this study, the cauliflower and white rice samples were burned, and the resulting energy was utilized to heat a specific amount of water. The temperature change (ΔT) of the water is used to calculate the energy in the sample. For the determination of ash content, the sample weight was recorded after a complete combustion inside the muffle furnace. As for the microbial activity, the sample of cauliflower and white rice were extracted with 50%,60%.70% concentrated ethanol. The pure culture of the microbes for Bacillus Subtilis and Salmonella Typhimurium was inoculated into the sterile nutrient broth to produce the bacterial inoculum. Agar diffusion method was used to detect the antibacterial activity of the samples. Cauliflowers show a relatively low value of calorie and ash content. The presence of a bioactive compound cannot be detected since there is no inhibition zone visible on the agar plate. As a result, the microbial activity of cauliflower and white rice cannot be determined.